EFFICACY OF PROPHYLACTIC USE OF ANTIBIOTICS TO AVOID FLARE-UP DURING NON-SURGICAL ROOT CANAL TREATMENT IN TYPE 2 CONTROLLED DIABETIC PATIENTS DIAGNOSED WITH SYMPTOMATIC APICAL PERIODONTITIS - Shaikh Zaid; Nadia Bashir; Sharjeel; Dr Hasan Afaq Zaidi; Muhammad Zohaib Younus; Moomal Aslam Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Non-surgical root canal therapy (NS-RCT) for symptomatic apical periodontitis (AP) is more likely to cause flare-ups in type 2 diabetics because to increased infection and inflammation. The role of prophylactic antibiotics in preventing these flare-ups remains uncertain. Objective: To evaluate the efficacy of antibiotics as a prophylactic measure to prevent flare-ups during non-surgical root canal treatment in patients with Type 2 controlled diabetics with symptomatic apical periodontitis. Methods: Department of Operative Dentistry and Endodontic, Institute of Dentistry, Liaquat University of Medical and Health Science Jamshoro/Hyderabad did this quasi-experimental research. Two groups were formed from 110 Type 2 controlled diabetics with symptomatic apical periodontitis receiving NS-RCT. The experimental group (n=55) received 2 gm. of Amoxicillin orally one hour before the first visit, whereas the control group (n=55) received no medicine. In this research, flare-up was defined as moderate to severe pain and swelling within 3 days after endodontic visit and required emergency treatment. Patients were instructed to call the operator if they experienced severe pain or swelling. Patients were reminded to return the proforma within 3 days. Results: The average age of the experiment group of patients was 41.53±8.21 years and in control group was 44.80±7.13 years. Rate of Flare-up was not statistically significant between groups (p=0.999). Conclusion: Prophylactic antibiotic treatment may not be necessary to prevent post-endodontic flare-ups in controlled type 2 diabetic patients undergoing non-surgical root canal treatment.